The Role of Peer-Based Reproductive Health Education in Improving the Knowledge and Attitudes of Adolescents and Pregnant Couples - Ahmad Daffa Izzulirfan (CV. Uruboros Publishing Group, 2025)
Reproductive health education is a strategic effort to improve the health quality of adolescents and couples of childbearing age. However, various challenges remain, such as low knowledge, attitudes that do not support healthy behaviors, and limited educational approaches that are appropriate to the characteristics of the target population. The peer-based approach is considered effective because it can create a more open, equal, and easily accepted communication atmosphere. This study aims to explore the role of peer-based reproductive health education in improving the knowledge and attitudes of adolescents and couples of childbearing age. The study used a qualitative approach with a descriptive design. Data were collected through in-depth interviews with adolescents and couples of childbearing age who participated in peer-based educational activities. The results show that the peer-based approach plays an important role in increasing understanding of reproductive health and forming more positive attitudes towards health behaviors. Equal interactions and shared experiences among peers encourage active participation and internalization of reproductive health values. This study concludes that peer-based reproductive health education has a significant contribution to improving the knowledge and attitudes of the target population, thus needing to be developed sustainably as a reproductive health promotion strategy.